The ethics of plea bargaining - Lippke, Richard L., 1954- (Oxford : Oxford University Press, 2011)
Plea bargaining is among the most controversial practices within the US criminal justice system. It offers the accused less punishment in exchange for an admission of guilt and can impose added punishment on those who insist on going to trial. This book offers an extended critical analysis of the ethics of the practice.
Description based on print version record.
Keywords: Plea bargaining; Plea bargaining -- Moral and ethical aspects